The Influence of Attitude and Perceived Risk to Optimize Intention to Adopt Based on Theory of Planned Behavior in Generation Z - Alifia Indah Putri Shaliha; Endy Gunanto Marsasi (UNIVED Press, 2024)
This study aims to determine the effect of attitude and perceived risk on intention to adopt based on the theory of planned behavior (TPB) in Generation Z. This study employs a quantitative methodology, utilizing a purposive sampling technique. The data utilized in this study is primary data, which was collected through the distribution of questionnaires. The study has a sample size of 210 respondents. The data was evaluated using Structural Equation Modeling (SEM) analysis with the use of AMOS 24 Graphics software. The findings of this study indicate that attitude is significantly influenced by perceived utility, perceived trust, and subjective norm. Furthermore, attitude significantly impacts the intention to adopt. The study's recent discoveries indicate that perceived danger exerts a detrimental and noteworthy impact on attitude, while perceived ease of use exerts a detrimental but inconsequential impact on attitude. The findings of this study emphasize the significance of comprehending customer risk perceptions in relation to service utilization. Companies should take into account the factors that impact consumer opinions. This can be accomplished by implementing effective marketing techniques, enhancing customer service, or providing an optimal user experience. This study provides an update on the variables by including the perceived risk variable to assess the perceived risk experienced by consumers.